Quality assessment of fresh meat cuts as a performance indicator of knives specifically adapted for robot-assisted operations - Helle Røer; Olga Korostynska; Frøydis Bjerke; Dmytro Romanov; Luis Eduardo Cordova-Lopez; Alex Mason; Per Håkon Bjørnstad; Torunn Thauland Håseth; Ole Alvseike (Management Science Letters, 2023)
Manual labour in slaughterhouses is hazardous work. Workers suffer from injuries and occupational illnesses resulting from repetitive movements with sharp knives. There is a need for a robotic tool which can perform versatile tasks with a high level of precision. This knife must be able to imitate the same primary cuttings of a professional butcher and produce meat products which are acceptable to the end-market. This paper reports the results of a world-wide assessment of the fresh pork meat cuts as a performance indicator of knives specifically adapted for automated operation. These knives included Victorinox knife, bespoke double bladed Uddeholm knife, vibrating knife and novel smart knife with built-in sensing mechanism that detects in real time the contact with meat and cut depth. Physical appearances of cuts were assessed anonymously by independent responders with different backgrounds. All knives were deemed acceptable in terms of cutting quality. There was also no discernible difference of opinion between manual and robot cuts. This indicates that the new knife for robot-assisted cutting is acceptable by market.